Antibiotic Susceptibility Profiles of Mycoplasma Hominis and Ureaplasma Urealyticum Isolated During a Population-Based Study Concerning Women Infertility in Northeast Romania - Mihai, Mareş (Sociedade Brasileira de Microbiologia, 2011)
The study was carried out on 1068 infertile women under initial evaluation. For Mycoplasma hominis, the highest resistance rates were registered for ciprofloxacin (72.22%), followed by macrolides and ofloxacin. For Ureaplasma urealyticum, the ciprofloxacin resistance was also high (51.72%), while the resistance rates to other tested antibiotics were significantly lower.